2005
DOI: 10.1002/app.21965
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, properties, and self‐assembly of poly(benzyl ether)‐b‐polystyrene dendritic–linear polymers

Abstract: Poly(benzyl ether)-b-polystyrene dendriticlinear polymers were successfully synthesized using a dendritic chloric poly(benzyl ether) (G 1 -Cl, G 2 -Cl, and G 3 -Cl) as the macroinitiator through the atom transfer radical polymerization process. The structure and properties of the resultant polymers were characterizated by gel permeation chromatography, 1 H-NMR, Fourier transform IR, thermogravimetric analysis, and differential scanning calorimetry. It was found that the temperature, reaction time, molar ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 79 publications
0
9
1
Order By: Relevance
“…Hyperbranched polymers are highly branched, polydisperse, three‐dimensional macromolecules that, because of their unique structures and properties, have attracted increasing attention 3–7. Compared to their linear analogues, hyperbranched polymers are expected to have different physical properties, such as a huge number of modifiable surface functionalities, lower viscosities, and better solubility 8–11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperbranched polymers are highly branched, polydisperse, three‐dimensional macromolecules that, because of their unique structures and properties, have attracted increasing attention 3–7. Compared to their linear analogues, hyperbranched polymers are expected to have different physical properties, such as a huge number of modifiable surface functionalities, lower viscosities, and better solubility 8–11.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to their linear analogues, hyperbranched polymers are expected to have different physical properties, such as a huge number of modifiable surface functionalities, lower viscosities, and better solubility 8–11. Although hyperbranched polymers are irregularly shaped and not perfectly symmetrical like dendrimers, they can be prepared in a single, one‐pot reaction, and this is the reason for relatively high interest in the industry of hyperbranched polymers 3–11. Moreover, as drug carriers, hyperbranched polymers can also offer their interior or peripheral functional groups to covalently fix drug molecules or, depending on their core–shell architecture, sequester guest molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the combination of dendritic and linear segments shows great promise as a functional class of block copolymers. [9][10][11][12][13][14][15][16][17] These dendritic-linear block copolymers offer the opportunity to combine the unique interfacial properties and high functionality of dendrimers with the phase separation behavior and processability of linear polymers. A number of solid-state morphological studies have recently been reported in which the dendritic-linear block copolymers have been shown to self-assemble into a wide range of microphase-separated domains including lamella, rods, and spheres.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the hyperbranched architecture with the perfect linear analogue suggests that the hyperbranched topology plays a crucial role in the host-guest encapsulation. Hyperbranched polymers are highly branched, polydispersed, threedimensional macromolecules, which, because of their unique structures and properties, have attracted increasing attention [3][4][5][6][7]. Compared to their linear analogs, hyperbranched polymers are expected to have different physical properties such as a huge number of modifiable surface functionality, lower viscosities and better solubility [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to their linear analogs, hyperbranched polymers are expected to have different physical properties such as a huge number of modifiable surface functionality, lower viscosities and better solubility [8][9][10][11]. Although hyperbranched polymers are of irregular shapes, and not perfectly symmetrical as dendrimers, they can be prepared in a single, one-pot reaction, which was the reason for the relatively high interest in the industry of hyperbranched polymers [3][4][5][6][7][8][9][10][11]. Moreover, as drug carriers, hyperbranched polymers can also offer their interior or peripheral functional groups to covalently fixate drug molecules or, depending on their core-shell architecture, to sequester guest molecules.…”
Section: Introductionmentioning
confidence: 99%